Numerical Groundwater Flow Modeling for The Intwrgranular Aquifer in Sarsian Sub-Basin, Dokan Lake, Iraqi Kurdistan Region - Ali, Salahalddin S.; Salley, Sardar Kaka Rash (Sulaimani Journal for Pure and Applied Sciences, 2013)
Sarsian sub-basin is located in the northeastern part of Iraq and to the northwest of Sulaimani governorate, north of Dokan dam between Northing (3987401–4006440) and Easting (498677–506055), covering an area of 99 km2. It is located within the Dokan reservoir catchment area. It extends on the left bank of the reservoir along the distance of 19 Km. The main aquifers in the studied area are integranular Quaternary aquifer and karstic to karstic fissured aquifer of Qamchuqa and part of Sarmord. Based on the analysis of the available water points, it was found that the general groundwater movement is from northeast to southwest, with two different directions; one unconfined and the other confined aquifer. Based on the well tests performed on 14 wells that penetrate the Quaternary aquifer, it was found that the hydraulic conductivity to be with median value of 3.445 m/d, transmissivity with median value of 382.95 m2/day and specific yield with median value of 0.1. Groundwater flow simulation was performed for the north part of Sarsian Sub-basin in both steady and transient states. The steady-state simulation is based on lower groundwater level (October 2009). A qualitative analysis of the map indicates that the simulated and the observed piezometric contours display the same pattern. The hydraulic gradients obtained from the simulated piezometry are similar to those of the observed piezometry in the whole study area. The model was run for four future scenarios of groundwater level. The first scenario of Dokan lake stage was simulated, and three stress periods of transient simulated with different volume of extraction per day. From the results, it is obvious that Dokan Lake stage has significant influence on the head fluctuations in the area.